Historical Forest Management Practices Influence Tree-Ring Based Climate Reconstructions - Skiadaresis, Georgios; Muigg, Bernhard; Tegel, Willy (Frontiers in Ecology and Evolution, 2021)
Tree-ring widths (TRW) of historical and archeological wood provide crucial proxies, frequently used for high-resolution multi-millennial paleoclimate reconstructions. Former growing conditions of the utilized trees, however, are largely unknown. Potential influences of historical forest management practices on climatic information, derived from TRW variability need to be considered but have not been assessed so far. Here, we examined the suitability of TRW series from traditionally managed oak forests (Quercus spp.) for climate reconstructions. We compared the climate signal in TRW chronologies of trees originating from high forests and coppice-with-standards (CWS) forests, a silvicultural management practice widely used in Europe for most of the common era. We expected a less distinct climate control in CWS due to management-induced growth patterns, yet an improved climate-growth relationship with TRW data from conventionally managed high forests. CWS tree rings showed considerably weaker correlations with hydroclimatic variables than non-CWS trees. The greatest potential for hydroclimate reconstructions was found for a large dataset containing both CWS and non-CWS trees, randomly collected from lumber yards, resembling the randomness in sources of historical material. Our results imply that growth patterns induced by management interventions can dampen climate signals in TRW chronologies. However, their impact can be minimized in well replicated, randomly sampled regional chronologies.